INFORMATION FOR THE IDENTIFICATION AND VERIFICATION OF PROSPECTIVE POVERTY SOCIAL ASSISTANCE RECIPIENTS - Aji Supriyanto; Sri Mulyani; Tri Ariyanto; Jeffri Alfa Razaq (Informatika, Universitas Jenderal Soedirman, 2023)
One important aspect of the poverty alleviation strategy is the availability of accurate poverty data, so that the government in providing social assistance (Bansos) can be right on target. The problem is that if there is an inaccuracy in the identification process when recording citizen data, it will affect the process of verifying and validating data on prospective Social Assistance recipients. Inaccuracies in prospective Social Assistance recipients can occur due to the process of collecting data on citizen identities and applying the wrong criteria for poverty requirements and the data is not up to date. The purpose of this research is to develop an information system to identify, verify, and validate data on prospective Social Assistance recipients. The identification stage for potential recipients of social assistance is carried out at the RT/RW and Kelurahan levels. The verification stage is carried out by fulfilling the requirements of the poverty criteria. Meanwhile, the validation stage is used to determine the ranking of potential social assistance recipients. The verification process is carried out at the Kelurahan and Kecamatan levels, while the validation process is at the Regency/City level. The waterfall method is used in the development of information system prototypes for prospective Social Assistance recipients with system analysis and design using use case, activity, and sequence diagrams. The prototype was tested with CRUD and trial & error, the result is a prototype system application that is able to collect citizen data by applying a priority scale for prospective recipients of social assistance based on a web by fulfilling the requirements of 14 poverty criteria according to the Central Statistics Agency (BPS).